Bicuspid Aortic Stenosis with and without Aortopathy: Considerations for Surgical Aortic Valve Replacement versus Transcatheter Aortic Valve Replacement. (2022) - Lee, Arthur J; Baig, Imran; Harrington, Katherine B; Szerlip, Molly
No abstract available